Perianesthesia management in laparotomy for patients with ileus obstruction leukocytosis using general anesthesia: A case report - Suandika Made; Handayani Rahmaya Nova; Ningrum Ema Wahyu; Dani Dwi Darmawan; Maharani Cindy; Sulaeman Ahmad (BIO Web of Conferences)
Obstructive ileus is a serious condition that requires immediate and appropriate management to prevent dangerous complications. This case study examines the management of perianesthesia in a patient with obstructive ileus and leukocytosis using general anesthesia. This research method used a descriptive observational design with a case study technique in a 22-year-old female patient who underwent laparotomy. Data were collected from the patient’s medical record, physical examination, laboratory results, and intensive monitoring of vital signs during the preoperative, intraoperative, and postoperative phases. Results showed that a comprehensive approach, which included fluid therapy, antibiotic selection, appropriate anesthesia induction, and careful postoperative monitoring, successfully stabilized the patient’s hemodynamics and decreased the risk of perioperative complications. Postoperative monitoring in the intensive care unit supports a better recovery process with maintained hemodynamic stability and vital signs. In conclusion, comprehensive perianesthesia management in this case provided a positive recovery prognosis. This study emphasizes the importance of collaboration between the surgical team and anesthesia team in managing obstructive ileus cases with leukocytosis and demonstrates the benefits of similar protocols for high-risk patients. In addition, further research is needed to develop more advanced anesthetic techniques in gastrointestinal conditions.